ChemInform Abstract: Recent Advances in Amino Acid N‐Carboxyanhydrides and Synthetic Polypeptides: Chemistry, Self‐Assembly and Biological Applications. Issue 10 (11th March 2014) - Lu, Hua; Wang, Jing; Song, Ziyuan; Yin, Lichen; Zhang, Yanfeng; Tang, Haoyu; Tu, Chunlai; Lin, Yao; Cheng, Jianjun
Abstract Review: 171 refs.